Evaluation for long term PM10 concentration forecasting using multi linear regression (MLR) and principal component regression (PCR) models - Abdullah S.; Ismail M.; Fong S.Y.; Ahmed A.M.A.N. (Thai Society of Higher Eduation Institutes on Environment, 2023)
air quality; atmospheric pollution; computer simulation; forecasting method; multiple regression; numerical model; particulate matter; policy implementation; pollution control; principal component analysis; Kuala Terengganu; Malaysia; Terengganu; West Malaysia